Pengembangan Video Animasi Kontekstual Berbantuan Animaker Untuk Meningkatkan Minat Belajar Siswa Pada Materi Perbandingan Kelas VII di MTsN 5 Tanah Datar - Fani Rahmadani; Isra Nurmai Yenti (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2026)
The low level of student interest in mathematics, particularly in the topic of ratios, among seventh-grade students at MTsN 5 Tanah Datar served as the background for this study. As a result of this low interest, students were not motivated or engaged in the learning process. The purpose of this study is to determine whether the use of contextual animated videos created with Animaker to increase students’ interest in learning about ratios is valid, beneficial, and effective. This study employs a research and development (R&D) design utilizing the 4-D development model—comprising the definition, design, development, and dissemination stages—as a framework. However, this study did not implement the dissemination stage. Questionnaires were used to collect data. The research instruments included a validation sheet, a teacher feedback questionnaire, a student feedback questionnaire, and a student learning interest questionnaire. Learning interest data were analyzed using N-Gain, while percentages were used to analyze data from the validation sheet, as well as the teacher and student feedback questionnaires. Based on the research findings, contextual animated videos created using Animaker have a very high validity rate of 90.8%. The results of the practicality test were classified as highly practical, with a teacher response rate of 88.75% and a student response rate of 83.96%. Meanwhile, this medium’s ability to increase learning interest resulted in a moderate N-Gain score of 0.63. Therefore, this medium is considered valid, useful, and sufficiently effective in increasing students’ learning interest.